2017
DOI: 10.5530/pc.2017.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitory Activity of Selected Australian Syzygium Species against Malodour Forming Bacteria

Abstract: Background: Extracts produced from S. australe and S. luehmannii fruit and leaves are potent growth inhibitors of many bacterial pathogens. They may also inhibit the growth of malodour producing bacteria and thus be useful deodorant components, although this is yet to be tested. Methods: S. australe and S. luehmannii fruit and leaf solvent extracts were investigated by disc diffusion assays against significant bacterial contributors to axillary and plantar malodour formation. Toxicity was determined using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…16 D. pruriens was deemed to be a good candidate for antibacterial screening due to its high antioxidant capacity, 25 as other high antioxidant plants have been reported to have noteworthy antibacterial activity. [32][33][34][35][36][37][38][39][40][41][42][43][44] Phenolic phytochemicals are generally strong antioxidants that protect cell constituents against oxidative damage by scavenging of free radicals, thereby averting their deleterious effects on nucleic acids, proteins and lipids in cells. 46 Interestingly, studies into the antioxidant/prooxidant effects of extracts from various plant species have demonstrated that the ability of a plant extract to exert antioxidant activity depends on multiple factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 D. pruriens was deemed to be a good candidate for antibacterial screening due to its high antioxidant capacity, 25 as other high antioxidant plants have been reported to have noteworthy antibacterial activity. [32][33][34][35][36][37][38][39][40][41][42][43][44] Phenolic phytochemicals are generally strong antioxidants that protect cell constituents against oxidative damage by scavenging of free radicals, thereby averting their deleterious effects on nucleic acids, proteins and lipids in cells. 46 Interestingly, studies into the antioxidant/prooxidant effects of extracts from various plant species have demonstrated that the ability of a plant extract to exert antioxidant activity depends on multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…have also been reported to have good anticancer 26 and antibacterial activities. [40][41][42][43] Kunzea pomifera F. Muell., Acronychia acidula F.; Muell.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity was assessed using an adapted Artemia franciscana nauplii lethality assay. 25 Briefly, 400 µL of seawater containing ~43 (mean 42.7, n = 125, SD 14.7) A. franciscana nauplii were added to wells of a 48 well plate and immediately used in the bioassay. Volumes of 400 µL of the reference toxin or the diluted plant extracts were transferred to the wells and incubated at 25 ± 1°C under artificial light (1000 Lux).…”
Section: Artemia Franciscana Nauplii Toxicity Screeningmentioning
confidence: 99%